2022
DOI: 10.3390/molecules27061900
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Constituent Spectra and Weighting in Extended Multiplicative Signal Correction in Infrared Spectroscopy

Abstract: Extended multiplicative signal correction (EMSC) is a widely used preprocessing technique in infrared spectroscopy. EMSC is a model-based method favored for its flexibility and versatility. The model can be extended by adding constituent spectra to explicitly model-known analytes or interferents. This paper addresses the use of constituent spectra and demonstrates common pitfalls. It clarifies the difference between analyte and interferent spectra, and the importance of orthogonality between model spectra. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Blazhko et al [ 43 ] proposed EMSA by improving the extended multiplicative signal correction (EMSC) [ 58 ] algorithm, and demonstrated that EMSA-augmented spectral data can effectively improve classification accuracy. EMSC processing of spectral data allows correcting for the effects of various physical and instrumental distortions, such as background and sample measurements of light source variations (baseline shifts), sample thickness variations (multiplicative effects), and instrumental scattering (spectral tilt) [ 59 ]. The basic model is as follows [ 58 ]: where is the measured spectrum; is the reference spectrum, usually the mean of all spectra; is the parameter associated with the baseline, multiplicative, linear and higher polynomials respectively; and is the residual.…”
Section: Methodsmentioning
confidence: 99%
“…Blazhko et al [ 43 ] proposed EMSA by improving the extended multiplicative signal correction (EMSC) [ 58 ] algorithm, and demonstrated that EMSA-augmented spectral data can effectively improve classification accuracy. EMSC processing of spectral data allows correcting for the effects of various physical and instrumental distortions, such as background and sample measurements of light source variations (baseline shifts), sample thickness variations (multiplicative effects), and instrumental scattering (spectral tilt) [ 59 ]. The basic model is as follows [ 58 ]: where is the measured spectrum; is the reference spectrum, usually the mean of all spectra; is the parameter associated with the baseline, multiplicative, linear and higher polynomials respectively; and is the residual.…”
Section: Methodsmentioning
confidence: 99%
“…Although molecular spectra are influenced by inter-molecular interactions , and environmental conditions (e.g., temperature and pH-value), several studies suggest that complex blood spectra can be described by linear superposition of individual single component spectra. For infrared spectroscopy, it is known that the strength of a molecular spectrum scales linearly with concentration over many orders of magnitude. , Furthermore, it has been shown that the concentration of several different molecules in blood can be determined by linear regression. Moreover, it was shown that a linear combination of the spectra of the most abundant molecular species can be used to describe experimentally observed differences in the spectra of blood serum from a healthy cohort and from patients with lung cancer …”
Section: Methodsmentioning
confidence: 99%
“…For infrared spectroscopy, it is known that the strength of a molecular spectrum scales linearly with concentration over many orders of magnitude. 3 , 28 Furthermore, it has been shown that the concentration of several different molecules in blood can be determined by linear regression. 29 32 Moreover, it was shown that a linear combination of the spectra of the most abundant molecular species can be used to describe experimentally observed differences in the spectra of blood serum from a healthy cohort and from patients with lung cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Extended multiplicative signal correction (EMSC) is used for eliminating uncontrollable path length or scattering effects. 23…”
Section: Methodsmentioning
confidence: 99%